Antiaging Potential of Lipophilic Extracts of Caulerpa prolifera - Gonçalo P. Rosa; Maria Carmo Barreto; Ana M. L. Seca; Diana C. G. A. Pinto (Marine Drugs)
The cosmeceutical industry has increasingly turned its attention to marine macroalgae, recognizing their significant bioactive potential as sources of natural compounds for skincare applications. A growing number of products now incorporate extracts or isolated compounds from various macroalgae species. However, many species remain underexplored, highlighting a valuable opportunity for further research. Among these, Caulerpa prolifera (Forsskål) J.V. Lamouroux has emerged as a promising candidate for cosmeceutical applications. This study provides the most comprehensive phytochemical assessment of C. prolifera to date, revealing its potential as a source of bioactive extracts and compounds. The analysis identified key components of its lipophilic profile, predominantly saturated and unsaturated fatty acids, alongside di-(2-ethylhexyl) phthalate—an endocrine disruptor potentially biosynthesized or bioaccumulated by the algae. While the crude extract exhibited moderate tyrosinase inhibitory activity, its overall antioxidant capacity was limited. Fractionation of the extract, however, yielded subfractions with distinct bioactivities linked to changes in chemical composition. Notably, enhanced inhibitory activities against elastase and collagenase were observed in subfractions enriched with 1-octadecanol and only traces of phthalate. Conversely, antioxidant activity diminished with the loss of specific compounds such as β-sitosterol, erucic acid, nervonic acid, and lignoceric acid. This work advances the understanding of the relationship between the chemical composition of C. prolifera and its bioactivities, emphasizing its potential as a source of cosmeceutical ingredients, leading to a more comprehensive valorization of this macroalga.